Caracterização do potencial de restauração vegetal em Unidades de Conservação de Proteção Integral e zonas de amortecimento no estado de São Paulo - Fernandes, Patrick Faria (2025)
The environmental degradation resulting from anthropogenic activities is a global concern due to its impacts on biodiversity and climate change. Restoring native vegetation in Integral Protection Conservation Units (UCPIs) and buffer zones (ZAs) is a promising strategy, however it faces challenges in identifying and quantifying the areas suitable for restoration, considering land division and environmental characterization. This project aimed to locate, quantify, and characterize areas eligible for restoration in 63 continental UCPIs and their respective ZAs in the State of São Paulo. The project was based on the integration of secondary geospatial data from official sources widely recognized in science. The areas eligible for restoration included pastures and land-use mosaics within the UCPIs, while in the ZAs, the stratification also considered Permanent Preservation Areas (APPs), Legal Reserves (RLs), and degraded pastures. For the characterization of the areas suitable for restoration, several variables were considered, such as proximity to remnants of native vegetation, biome, agricultural suitability, and slope. The land situation of the UCPIs was classified as public and private areas, while in the ZAs, areas were categorized by property size. The definition of the restoration method was based on probability of regeneration: i) 0 to 40%: planting; ii) 41 to 70%: assisted regeneration; iii) 71 to 100%: natural regeneration without assistance. For non-mechanizable areas (slope > 20%) and areas without viable natural regeneration, direct seeding was adopted. A total of 185,113.57 ha suitable for restoration were identified, representing 12.34% of the 1.5 millionhectare target of the São Paulo Climate Action Plan. In the UCPIs, 33,973.40 ha were identified, of which 46.70% were public domain, 25.32% private domain, and 27.98% undefined domain, with a potential for native vegetation expansion of 3.90%. The ZAs covered 151,140.17 ha, divided into 64,526.90 ha of APPs, 28,059.58 ha of RLs, and 65,691.19 ha of degraded pastures, with a potential increase of 16.43% in vegetation cover. Of these areas, 75.88% are in large properties while 24.12% are in areas with no information. The characterization highlighted positive aspects, such as the expansion of native vegetation remnants and proximity to nurseries. Regarding methods, natural regeneration without assistance predominated in the UCPIs (58.03%), while planting was more common in the ZAs (54.94%). In both categories, assisted regeneration and direct seeding had similar proportions. Finally, this study highlights the great potential of UCPIs and ZAs in environmental restoration, emphasizing their crucial role in meeting the established goals. The proposed methodology offers a practical, replicable, and feasible approach for implementing and managing restoration actions, providing valuable input for the development of more effective public policies and contributing to climate change mitigation and the improvement of environmental policies in Brazil.